Genetic manipulation of Schistosoma haematobium, the neglected schistosome. - Gabriel Rinaldi; Tunika I Okatcha; Anastas Popratiloff; Mary A Ayuk; Sutas Suttiprapa; Victoria H Mann; Yung-san Liang; Fred A Lewis; Alex Loukas; Paul J Brindley (Public Library of Science (PLoS), 2011)
Minimal information on the genome and proteome of Schistosoma haematobium is available, in marked contrast to the situation with the other major species of human schistosomes for which draft genome sequences have been reported. Accordingly, little is known about functional genomics in S. haematobium, including the utility or not of RNA interference techniques that, if available, promise to guide development of new interventions for schistosomiasis haematobia.Here we isolated and cultured developmental stages of S. haematobium, derived from experimentally infected hamsters. Targeting different developmental stages, we investigated the utility of soaking and/or square wave electroporation in order to transfect S. haematobium with nucleic acid reporters including Cy3-labeled small RNAs, messenger RNA encoding firefly luciferase, and short interfering RNAs (siRNAs). Three hours after incubation of S. haematobium eggs in 50 ng/µl Cy3-labeled siRNA, fluorescent foci were evident indicating that labeled siRNA had penetrated into miracidia developing within the egg shell. Firefly luciferase activity was detected three hours after square wave electroporation of the schistosome eggs and adult worms in 150 ng/µl of mRNA. RNA interference knockdown (silencing) of reporter luciferase activity was seen following the introduction of dsRNA specific for luciferase mRNA in eggs, schistosomules and mixed sex adults. Moreover, introduction of an endogenous gene-specific siRNA into adult schistosomes silenced transcription of tetraspanin 2 (Sh-tsp-2), the apparent orthologue of the Schistosoma mansoni gene Sm-tsp-2 which encodes the surface localized structural and signaling protein Sm-TSP-2. Together, knockdown of reporter luciferase and Sh-tsp-2 indicated the presence of an intact RNAi pathway in S. haematobium. Also, we employed laser scanning confocal microscopy to view the adult stages of S. haematobium.These findings and approaches should facilitate analysis of gene function in S. haematobium, which in turn could facilitate the characterization of prospective intervention targets for this neglected tropical disease pathogen.